Exercise and the Immune System: Regulation, Integration, and Adaptation - Klarlund Pedersen, B.; Hoffmann-Goetz, L. (Physiological Reviews, 2000)
Stress-induced immunological reactions to exercise have stimulated much research into stress immunology and neuroimmunology. It is suggested that exercise can be employed as a model of temporary immunosuppression that occurs after severe physical stress. The exercise-stress model can be easily manipulated experimentally and allows for the study of interactions between the nervous, the endocrine, and the immune systems. This review focuses on mechanisms underlying exercise-induced immune changes such as neuroendocrinological factors including catecholamines, growth hormone, cortisol, b-endorphin, and sex steroids. The contribution of a metabolic link between skeletal muscles and the lymphoid system is also reviewed. The mechanisms of exercise-associated muscle damage and the initiation of the inflammatory cytokine cascade are discussed. Given that exercise modulates the immune system in healthy individuals, considerations of the clinical ramifications of exercise in the prevention of diseases for which the immune system has a role is of importance. Accordingly, drawing on the experimental, clinical, and epidemiological literature, we address the interactions between exercise and infectious diseases as well as exercise and neoplasia within the context of both aging and nutrition.